Major complications after tongue-tie release: A case report and systematic review. (November 2020) - Solis-Pazmino, Paola; Kim, Grace S.; Lincango-Naranjo, Eddy; Prokop, Larry; Ponce, Oscar J.; Truong, Mai Thy
Abstract: Introduction: The diagnosis of ankyloglossia, or tongue-tie, and the number of frenotomies performed has increased over 10-fold from 1997 to 2012 in the United States. The sharpest increase has been in neonates. For parents considering frenotomy for their breastfeeding newborn, there is controversy surrounding the evaluation of tongue-tie and the benefit of a frenotomy. Complications from tongue-tie procedures are thought to be low, though it is not well reported nor studied. Objectives: The aim of this study is to describe a case of a sublingual mucocele after laser frenotomy in a neonate with tongue-tie and to investigate major complications reported after tongue-tie release in pediatric patients through a systematic review of the literature. Case report: We present a 6-week-old female who underwent a laser frenotomy procedure performed by a dentist who presented with a new cyst under her tongue. Material and methods: A systematic literature search of articles published from 1965 to April 2020 was conducted in Ovid MEDLINE(R), Ovid EMBASE, and Scopus. Citations were uploaded into a systematic review software program (DistillerSR, Ottawa, ON, Canada), followed by full text screening. Results: 47 major complications were reported in 34 patients, including our patient. Most of the cases were located in the United States and Europe. The most frequent indications for the procedure were breastfeeding problems (n = 18) and speech impediment (n = 4). The procedure was performed by dentists (n = 6), lactation consultants (n = 5), and otolaryngologists (n = 4). The bulk of the major complications after frenotomy included poor feeding (n = 7), hypovolemic shock (n = 4), apnea (n = 4), acute airway obstruction (n = 4), and Ludwig angina (n = 2). Conclusions: Reporting of complications after frenotomy is lacking. Risks to neonates may be different than risks to older children and adults. Practitioners across different specialties should be monitoring and studying this more rigorously to better guide patients and families on the risks and benefits of this procedure.